UPAYA PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MTS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Fatimah, Ade Evi (Mahesa Research Center, 2020)
The purpose of this study is to improve the mathematical problem-solving ability of students in class VII-1 MTs Islamiyah Medan through the STAD type cooperative learning model. This research is a Class Action Research (CAR). The subjects of this study were 40 students of grade VII-1 MTs Islamiyah Medan. The object in this study is to improve students' mathematical problem-solving abilities through the STAD Type Cooperative learning model on the subject of rectangular flat shapes. This research instrument uses tests of mathematical problem-solving abilities, observation, and interviews. Based on the preliminary results of the interviews conducted with the mathematics teacher, it was obtained that the mathematical problem-solving ability of students in class VII-1 MTs Islamiyah Medan was still not optimal. From the data obtained only 17.5% of students met the mathematical problem-solving ability criteria. This research was conducted in two cycles by providing treatment using STAD learning. Based on the results of data analysis students' mathematical problem-solving abilities in the first cycle obtained that 70% of students meet the criteria. But because it has not reached 85% completeness then continued with the second cycle. In the second cycle, 90% of students who met the criteria of mathematical problem-solving ability were obtained. The conclusion of this study is an increase in students' mathematical problem-solving abilities from cycle I to cycle II.